Application of six sigma techniques in a manufacturing company - Lau, Kah Wei, 1990-, author 635144; Wong, Kuan Yew, supervisor 185071; Fakulti Kejuruteraan Mekanikal 8081 (2014)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2014